Performance Analysis of Piezoelectric Multi-cantilever Array System with Different Mass Configurations - Syed, Fahmidul Huq; Li Wah Thong; Yee Kit Chan (International Journal of Integrated Engineering, 2024)
This paper presents a piezoelectric array harvester using five array beams with piezo patches on their fixed ends and tip masses situated on various locations on the beams. The simulation-based study is conducted in COMSOL Multiphysics within a range of 0-40 Hz to inspect and evaluate the bandwidth frequency of the voltage output. Three different categories A, B & C have been studied including three different materials, tungsten, steel, and aluminium used on the array beams and the tip mass to investigate the effect of the weight and the location of the tip mass on the beam. Additionally, twenty sub-categories of configuration of the tip mass have been presented and evaluated in the paper. The collected data from different arrangements of the block masses and the use of different materials helped conclude the correlation among the location, weight of the tip mass, the magnitude of outcome and resonant frequencies. The paper identifies potential arrangements of multi-cantilever array system to broaden the bandwidth frequency.